Extracellular vesicle lyophilization for enhanced distribution to the point of care - Morgane E. Golan; Steven L. Stice (Extracellular Vesicle)
Therapeutic extracellular vesicles (EVs) are in clinical trials and if successful, EVs wider use will be largely affected by costs to patients/insurers and accessibility. EV preservation-storage efficiencies directly factor into both of these considerations. EV cryopreservation drives up costs and relies on the pharmaceutical cold chain, which is expensive and among the most pressing barriers to widespread access of medicines. Lyophilization preserves biological materials at room temperature, thereby enhancing storage while circumventing the cold chain. Here we describe the factors influencing EV storage and lyophilization processes which may improve accessibility of EV therapies.